MAKNA PLURALISME PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Khoiriyah Khoiriyah; Devy Habibi Muhammad (IMTIYAZ: Jurnal Ilmu Keislaman, 2018)
Religious Education conventionally serves to create children with strong faith and devotion, as well as novel behavior, so that they can live within their society peacefully and happily, without any severe difficulty. In other words, religious education can help learners in building religious community. Religious society basically has a broad sense, but often understood with limited understanding, in terms of people who only show obedience in performing religious rituals only. Beside its function to build a society that will obey the teachings of their religion, religious education is expected to play a role building a humanist and pluralist society. This article tries to describe how religious education plays such role in multicultural country like Indonesia.